The Australian child support reforms: a critical evaluation. Issue 3 (October 2015) - Smyth, Bruce; Rodgers, Bryan; Son, Vu; Vnuk, Maria
Abstract : The Australian Child Support Scheme aims to ensure that children continue to be supported financially should their parents separate or never live together. Sweeping changes to the Australian Child Support Scheme were introduced between 2006 and 2008, featuring a dramatically different system for the calculation of child support and a more rigorous enforcement regime. The reforms were intended to respond to ongoing concerns about equity, and to changes in social expectations and practices in gender, work, and parenting. In this article we summarise key findings from a large cross‐sequential study of the child support reforms. Although the new formula initially led to lower child support payments, and an increase in the proportion of separated mothers experiencing income disadvantage, payments two years later had increased slightly. More broadly, the new scheme appears to have resulted in little change in separated parents' policy knowledge, parenting arrangements, perceptions of fairness, and child support compliance. Taken together, these findings suggest that Australia may not have made as much progress as it would have liked in this thorny area of social policy – especially in relation to compliance and perceptions of fairness.